Ventilatory Management During Normothermic Ex Vivo Lung Perfusion: Effects on Clinical Outcomes. Issue 5 (May 2016) - Terragni, Pier Paolo; Fanelli, Vito; Boffini, Massimo; Filippini, Claudia; Cappello, Paola; Ricci, Davide; Del Sorbo, Lorenzo; Faggiano, Chiara; Brazzi, Luca; Frati, Giacomo; Venuta, Federico; Mascia, Luciana; et al.
Abstract : Background: During ex vivo lung perfusion (EVLP), fixed ventilator settings and monitoring of compliance are used to prevent ventilator-induced lung injury (VILI). Analysis of the airway pressure-time curve (stress index) has been proposed to assess the presence of VILI. We tested whether currently proposed ventilator settings expose lungs to VILI during EVLP and whether the stress index could identify VILI better than compliance. Methods: Flow, volume, and airway opening pressure were collected continuously during EVLP. Durations of mechanical ventilation, intensive care unit (ICU) and hospital lengths of stay were recorded in lung recipients. Results: Fourteen lungs underwent EVLP and were transplanted. In 5 lungs, 95 ± 2% of the stress index values were within the 0.95 to 1.05 range (protected); in the remaining nine lungs, 69 ± 1% of the values were greater than 1.05 and 15 ± 3% were less than 0.95 (nonprotected). There was a significant ( P < 0.05) increase in cytokine concentrations after 4 hours of EVLP in the nonprotected lungs. Durations of mechanical ventilation, ICU, and hospital lengths of stay were shorter in recipients of protected than that of nonprotected lungs ( P < 0.05). There was no correlation between compliance during EVLP and duration of mechanical ventilation or ICU and hospital lengths of stay in recipients, but the stress index during EVLP was significantly correlated with the duration of mechanical ventilation and with ICU and hospital lengths of stay ( P < 0.05). Conclusions: This small, preliminary study shows that ventilator settings currently proposed for EVLP may expose lungs to VILI. Use of the stress index to personalize ventilator settings needs to be tested in further clinical studies. Abstract : This study shows that ventilator settings currently proposed for ex-vivo lung perfusion (EVLP) may expose lungs to ventilator-induced lung injury (VILI) and use of the airway pressure-time curve (stress index) to personalize ventilator settings could reduce VILI in clinical lung transplantation.